CADANGAN ASURANSI DWIGUNA LAST SURVIVOR DENGAN METODE PREMIUM SUFFICIENCY - Margaretta Tiolina Siregar; Hasriati '; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses premium sufficiency method which is used to determine the reserved gross premium of an endowment life insurance with last survivor status. The calculation of gross premium is obtained by determination of the present value of due life annuity and net premium by members of life insurance. The present value of due life annuity and net premium are expressed in the form of commutation function.